2014
DOI: 10.1037/a0037428
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering, cognition, and performance: A theory-driven meta-analysis of attention regulation.

Abstract: The current meta-analysis accumulates empirical findings on the phenomenon of mind-wandering, integrating and interpreting findings in light of psychological theories of cognitive resource allocation. Cognitive resource theory emphasizes both individual differences in attentional resources and task demands together to predict variance in task performance. This theory motivated our conceptual and meta-analysis framework by introducing moderators indicative of task-demand to predict who is more likely to mind-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
232
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(282 citation statements)
references
References 114 publications
17
232
6
Order By: Relevance
“…Numerous studies have investigated mind wandering across a range of tasks and have found that it occurs anywhere between 20%-50% of the time (Kane et al, 2007;Killingsworth & Gilbert, 2010;Schooler, Reichle, & Halpern, 2004;Smilek, Carriere, & Cheyne, 2010). Multiple studies (Feng, D'Mello, & Graesser, 2013;Robertson, Manly, Andrade, Baddeley, & Yiend, 1997;Seibert & Ellis, 1991;Smallwood et al, 2004;Smallwood, Fishman, & Schooler, 2007;Smallwood & Schooler, 2006), including a recent meta-analysis of 49 research reports (Randall, Oswald, & Beier, 2014), have indicated that mind wandering during a task is negatively related with task performance. For instance, mind wandering is negatively correlated with text comprehension, partly because textual information is not integrated with the mental model of the text when the reader is mind wandering (Feng et al, 2013;Smallwood, 2011).…”
Section: Abstract Mind Wandering Reading Eye Gaze Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated mind wandering across a range of tasks and have found that it occurs anywhere between 20%-50% of the time (Kane et al, 2007;Killingsworth & Gilbert, 2010;Schooler, Reichle, & Halpern, 2004;Smilek, Carriere, & Cheyne, 2010). Multiple studies (Feng, D'Mello, & Graesser, 2013;Robertson, Manly, Andrade, Baddeley, & Yiend, 1997;Seibert & Ellis, 1991;Smallwood et al, 2004;Smallwood, Fishman, & Schooler, 2007;Smallwood & Schooler, 2006), including a recent meta-analysis of 49 research reports (Randall, Oswald, & Beier, 2014), have indicated that mind wandering during a task is negatively related with task performance. For instance, mind wandering is negatively correlated with text comprehension, partly because textual information is not integrated with the mental model of the text when the reader is mind wandering (Feng et al, 2013;Smallwood, 2011).…”
Section: Abstract Mind Wandering Reading Eye Gaze Machine Learningmentioning
confidence: 99%
“…To establish convergent validity, we correlated the proportion of cases that the gaze-based detector denoted as mind wandering with self-reported mind-wandering proportions. Predictive validity was obtained by correlating gaze-based mind wandering with text comprehension scores, which has been shown to be negatively related with self-reported wandering Faber, Mills, Kopp, & D'Mello, 2016;Feng et al, 2013;Randall et al, 2014;Unsworth & McMillan, 2013).…”
Section: Eye Gaze Correlates Of Mind Wanderingmentioning
confidence: 99%
“…It should be noted that although the magnitude of the correlation between working memory capacity and mind-wandering in the noise condition is small and not significant (r = 0.06), a recent review(Randall, Oswald, & Beier, 2014) indicated a point estimate of ρ = À0.14 between cognitive abilities and mind-wandering. So the lack of a correlation here is possibly due to low power to detect this small effect.…”
mentioning
confidence: 92%
“…It has been shown that mind wandering results in increased error rates during signal detection tasks (Robertson et al 1997;Smallwood et al 2004), lower recall during memory tasks (Seibert and Ellis 1991;Smallwood and Schooler 2006), and poor comprehension during reading tasks (Feng et al 2013;Smallwood et al 2007). In addition, a recent meta-analysis of 49 independent samples found that mind wandering was consistently negatively correlated with performance across a range of tasks (Randall et al 2014). Based on this research, it is evident that performance on tasks that require attentional focus can be hindered by off task thoughts (i.e., mind wandering).…”
Section: Introductionmentioning
confidence: 99%